“Not in their right mind”: the relation of psychopathology to the quantity and quality of creative thought - Ramey, Christopher H.; Chrysikou, Evangelia G. (Frontiers in Psychology, 2014)
The empirical link between psychopathology and creativity is often correlational and fraught with suspiciously causal interpretations. In this paper, we review research in favor of the position that certain forms of psychopathology that profoundly affect the neural substrates for rule-based thought (e.g., schizophrenia, bipolar disorder) can significantly influence the quantity of creative production. Because highly productive individuals, irrespective of psychopathology, often produce work of greater quality, it seems that such an increase in the quantity of one’s output positively affects the likelihood of generating those statistically rare acts and achievements identified and celebrated as creative. We consider evidence that offers support for such a claim. In addition, we explore findings from neuroscience that can address how a neural mechanism, the flexibility of which relies on tradeoffs between rule-based (e.g., prefrontal cortex) and stimulus-based (e.g., sensorimotor cortex) brain regions, is influenced by psychopathology in ways that can alter dramatically the quantity and quality of creative output.